2017
DOI: 10.3892/ol.2017.6134
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of sphingosine kinase 1 is predictive of poor prognosis in human breast cancer

Abstract: Sphingosine kinase 1 (SPHK1) is a bioactive lipid mediator that has been identified as a biomarker in various cancers and is considered to play an important role in tumor progression. In the present study, the expression level of SPHK1 was examined in breast cancer clinical specimens, and its association with patient survival was investigated to clarify the clinical significance of SPHK1 in breast cancer. SPHK1 mRNA expression was increased in breast cancer tissues compared with that in matched adjacent breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Guan et al (31) reported that sphingosine kinase 1 expression in thyroid cancer is up-regulated and associated with expression of proliferating cell nuclear antigen and showed that silencing of sphingosine kinase 1 suppresses proliferation of thyroid cancer cells. Other studies have shown that increased sphingosine kinase 1 expression is associated with lymph node metastasis and distant metastasis of breast cancer (36). These findings are consistent with our data showing that high sphingosine kinase 1 expression is associated with aggressive oncogenic behavior including tumor multiplicity, extrathyroidal extension, and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 83%
“…Guan et al (31) reported that sphingosine kinase 1 expression in thyroid cancer is up-regulated and associated with expression of proliferating cell nuclear antigen and showed that silencing of sphingosine kinase 1 suppresses proliferation of thyroid cancer cells. Other studies have shown that increased sphingosine kinase 1 expression is associated with lymph node metastasis and distant metastasis of breast cancer (36). These findings are consistent with our data showing that high sphingosine kinase 1 expression is associated with aggressive oncogenic behavior including tumor multiplicity, extrathyroidal extension, and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 83%
“…SphK is increased in breast cancer [46,47] and is activated by cytokines, resulting in increases in intracellular S1P [48]. SphK-induced S1P accumulation suppresses apoptosis [49].…”
Section: Pathogenic Stimulusmentioning
confidence: 99%
“…Overexpression of SPHK1 is associated with tumorigenic cell behavior that involves promoting cell growth, migration, and inhibiting apoptosis [24][25][26][38][39][40][41]44]. Recent studies also indicated that SPHK1-S1P may play a role in regulating CSCs populations in breast cancer models.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that increased SPHK1 activity promotes cancer cell growth, metastasis, and inhibits apoptosis [24][25][26][38][39][40][41]. Indeed, high expression of SPHK1 in tumors is associated with worse prognosis and overall outcomes in breast cancer patients [41][42][43][44][45][46][47][48]. In addition, overexpression of SPHK1 in breast cancer cells was reported to increase breast CSCs and the tumorigenicity of tumors in nude mice via S1P binding to S1P 3 and down-stream stimulation of Notch and p38 MAPK signaling [49].…”
Section: Introductionmentioning
confidence: 99%